Sex-based variations in breath-holding: oxygen storage and diving response among non-divers - Pernett, Frank; Schagatay, Erika; Holmström, Pontus (Frontiers in Physiology, 2025)
Breath-hold diving performances are typically better in men than in women. However, it is still being determined if there are differences in the physiological responses to breath-holding between the sexes. We conducted a study comparing the maximum breath-hold duration, heart rate (HR) reduction, peripheral oxygen saturation (SpO2), and spleen volume and contraction in 37 men and 44 women, all of whom had no prior breath-holding experience. They performed two dry apneas separated by 2 min; the first was limited to 60 s, followed by a maximal effort apnea. HR and SpO2 were measured continuously. Spleen diameters were measured via ultrasonography before and immediately following each apnea. The maximal apneic duration was longer in men (78 ± 19 s) compared with women (61 ± 18 s, p < 0.001), while the HR reduction was similar (women: 16% ± 19% versus men: 16% ± 17%, p = 0.973). The absolute splenic contraction was greater in men (59 ± 56 mL) compared with women (35 ± 28 mL, p < 0.001) in the first apnea, while the relative contraction was similar (women: 21% ± 17% versus men: 23% ± 13%, p = 0.528). In addition, the lowest SpO2 during the maximal apnea was similar between sexes (women: 93.3% ± 4.4%; men: 91.9% ± 4.3%, p = 0.161). We conclude that men have larger spleen size and contraction, lung size, and maximal apneic duration than women. The cardiovascular diving response is similar between sexes for those inexperienced with apneic diving. The longer breath-hold duration in men may be partly due to greater oxygen storage capacity, which results from larger vital capacity and greater spleen size and contraction.